NIKAH MISYAR ANTARA KEMASLAHATAN DAN KEMUDARATAN: TINJAUAN MAQĀṢID AL-SYARĪ‘AH - Fauzul Kabir; Wulandari, Niken Retno (Wasīlah: Journal Of Sharia Sciences, 2026)
Misyar marriage is a contemporary phenomenon in Islamic family law that continues to generate scholarly debate due to its divergence from conventional marital arrangements, particularly in relation to the fulfillment of spousal rights and obligations. This article analyzes misyar marriage through the lens of Islamic legal philosophy by examining the interaction between normative legal validity, ethical considerations, and the objectives of Islamic law (maqāṣid al-sharīʿah). The study adopts a normative-theological legal method based on library research and employs a descriptive-analytical approach to assess classical and contemporary legal opinions. The findings indicate that misyar marriage is normatively valid because it fulfills the essential pillars and legal requirements of marriage as recognized in Islamic jurisprudence. Nevertheless, when evaluated from the maqāṣid perspective, misyar marriage presents an ambivalent position between potential benefit (maṣlaḥah) and harm (mafsadah). Consequently, this form of marriage should not be widely promoted and may only be justified under conditions of necessity, accompanied by strict moral responsibility and legal supervision to safeguard the fundamental objectives of Islamic family law.